2011
DOI: 10.1128/jb.00919-10
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Parasitism by Simkania negevensis ( Chlamydiae )

Abstract: Intracellular bacteria live in an environment rich in most essential metabolites but need special mechanisms to access these substrates. Nucleotide transport proteins (NTTs) catalyze the import of ATP and other nucleotides from the eukaryotic host into the bacterial cell and render de novo synthesis of these compounds dispensable. The draft genome sequence of Simkania negevensis strain Z, a chlamydial organism considered a newly emerging pathogen, revealed four genes encoding putative nucleotide transport prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 81 publications
0
38
0
Order By: Relevance
“…In S. negevensis, entry in the citrate cycle can occur: (a) through acetyl-CoA produced from pyruvate following glycolysis and (b) through the transformation of asparagine in fumarate (Collingro et al, 2011;Omsland et al, 2014). Moreover, Waddliaceae, Parachlamydiaceae and Simkaniaceae are able to synthetize NAD þ from nicotinamide (Bertelli et al, 2010;Omsland et al, 2014) and S. negevensis can, additionally, use asparagine as a source of NADþ (Collingro et al, 2011;Knab et al, 2011;Omsland et al, 2014). Finally, an in vitro experiment by Kahane et al suggests that S. negevensis is able to grow in a glucose free medium; indeed the number of infectious forming units was similar using a Roswell Park Memorial Institute (RPMI) media depleted in glucose and supplemented with 1% glucose .…”
Section: Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…In S. negevensis, entry in the citrate cycle can occur: (a) through acetyl-CoA produced from pyruvate following glycolysis and (b) through the transformation of asparagine in fumarate (Collingro et al, 2011;Omsland et al, 2014). Moreover, Waddliaceae, Parachlamydiaceae and Simkaniaceae are able to synthetize NAD þ from nicotinamide (Bertelli et al, 2010;Omsland et al, 2014) and S. negevensis can, additionally, use asparagine as a source of NADþ (Collingro et al, 2011;Knab et al, 2011;Omsland et al, 2014). Finally, an in vitro experiment by Kahane et al suggests that S. negevensis is able to grow in a glucose free medium; indeed the number of infectious forming units was similar using a Roswell Park Memorial Institute (RPMI) media depleted in glucose and supplemented with 1% glucose .…”
Section: Metabolismmentioning
confidence: 99%
“…Four isoforms of nucleotides transporters have been identified in S. negevensis: SnSTT1, an ADP/ATP antiporter; SnSTT2, a guanine/ATP/ H þ symporter; SnSTT3 a global nucleotide triphosphate antiporter, also able to transport deoxy-CTP (dCTP). The function of the last transporter, SnSTT4, is unknown (Knab et al, 2011). The ability to transport dCTP is unique among prokaryotes and might represent a selective metabolic advantage for S. negevensis, favoring its relative growth in environments rich in cytosine.…”
Section: Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…In these organisms, essential metabolic pathways are often truncated or missing completely, and hence, import of intermediates or products is of high physiological importance. In the past years, several carrier proteins that mediate the provision of diverse metabolically relevant molecules and thus compensate for the reduced biosynthetic activity in intracellular bacteria have been identified (15,16,(23)(24)(25)(26)(27)(28)(29)43). Analysis of the genome of A. asiaticus revealed that its size is comparable to those of other intracellular bacteria; however, it encodes an unusually small number of proteins involved in metabolic processes (32).…”
Section: Discussionmentioning
confidence: 99%
“…A reduced genome size accompanied by the loss of biosynthetic pathways and the recruitment of carriers for compensation for missing or truncated metabolic pathways is a characteristic common feature of Chlamydiales and Rickettsiales (21,22): specific nucleotide transporters were shown to allow energy parasitism and complementation of missing purine and pyrimidine nucleotide or cofactor biosynthesis pathways (23)(24)(25)(26)(27)(28)(29). Deciphering of more and more genomes demonstrated that many intracellular bacteria are biosynthetically highly impaired.…”
mentioning
confidence: 99%